Understanding property rights - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
People often think of property rights in a narrow sense as ownership - the right to completely and exclusively control a resource. However, property rights are better understood as overlapping “bundles” of rights.